من أنماط الخطاب في الن النّفري)ت354ه( أنموذج - ضيفاو ي, الساسي بن محمد (University of El-oued, 2021)
لملخص ملخّص لعلّ روعة النصّ الصوفي وبصفة خاصّة النصّ النفري، تبدو في هُويته المتحرّكة وفي تنوّع خطاباته وتعدّد أنماط معجمه وخصوبة متنه، ويتبدّى ذلك من خلال عبارته التي لا تستقرّ على حال بل هي متموّجة تنوس بين التغير والثبات والظاهر والضامر والحقيقة والمجاز، ومن ثمّة كان لزاما على الباحث أن يميّز بين الأصلي والفرعي وبين الحقيقي والوهمي وبين الحسّي والمعنوي وبين الخاص والعام في هذا الجنس من الكتابات المخصوصة في ضوء أنساق المتن الصوفي، والنصّ النفّري بالتحديد وصفا وسردا وحجاجا Abstract Maybe the magnificence of the mystic script, particularly Nifari,s/scripts manifests itself in its dynamic essence and in the variability of its types of semantic terminology. The latter is obvious through its lexics which don’t settle down to a specific status, but it is oscillating between its variability and persistence; the apparent and the implicit meaning as well. Relying on these facts, the researcher has to distinguish between what is emotional and what is moral, as far the mystic texts is concerned.
One of the types od discourse in the soufi text Al-Anfry (d. 354 AH) is a model
مقال. Ex Professo. مج6. ع.1. جامعة الوادي
Keywords: الكلمات ة ّ املفتاحي : التصوف؛ الخطاب؛ النفري؛ املخاطبة؛ الرموز; Keywords: Mysticism; Discourse; Nifari; Sufi-addressing; Symbols.